2017
DOI: 10.1186/s12906-017-1582-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenolic constituents of daylily flowers on corticosterone- and glutamate-treated PC12 cells

Abstract: BackgroundDaylily flowers, the flower and bud parts of Hemerocallis citrina or H. fulva, are well known as Wang-You-Cao in Chinese, meaning forget-one’s sadness plant. However, the major types of active constituents responsible for the neurological effects remain unclear. This study was to examine the protective effects of hydroalcoholic extract and fractions and to identify the active fractions.MethodsThe extract of daylily flowers was separated with AB-8 resin into different fractions containing non-phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…There was a positive correlation between antioxidant activity and total phenolic and flavonoid content [ 15 , 16 ]. Our results indicated that HCEA had higher flavonoid and total phenolic levels than the other extract fractions did.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a positive correlation between antioxidant activity and total phenolic and flavonoid content [ 15 , 16 ]. Our results indicated that HCEA had higher flavonoid and total phenolic levels than the other extract fractions did.…”
Section: Resultsmentioning
confidence: 99%
“…Hemerocallis citrine Baroni (daylily) is a perennial herb of the Liliaceae family [ 14 ], which is indigenous to Asia, and its flowers are used for ornamental purposes and as food and medicine. According to previous studies, Hemerocallis fulva has been used to treat various diseases including depression [ 15 ], inflammation [ 16 ], insomnia [ 17 ], hepatosis [ 18 ], and cancer [ 19 ]. However, no studies have shown the hepatoprotective activity of H. citrine Baroni or any potential mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Flower of daylily ( Hemerocallis fulva L., Figure ) is a vegetable commonly consumed in Asia countries including China and Taiwan. It is reported that daylily flower ethanol extract (EE) displayed free radical scavenging effects in HepG2 cells (Lin, Lu, Huang, & Chen, ); and alleviated neurotoxicity in PC12 cells treated with corticosterone or glutamate (Tian et al., ). The animal studies of Lin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Another name is Wang-You Cao, which in Chinese means "forget-one's sadness" plant [8]. Daylily has been used to treat a wide variety of conditions such as depression, jaundice and insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Daylily has been used to treat a wide variety of conditions such as depression, jaundice and insomnia. More recently, Daylily has been shown to have neuroprotective properties, which were demonstrated by significantly reversing corticosterone and glutamate-induced neurotoxicity in a dose-dependent manner [8]. Daylily buds have also been shown to have a powerful effect as a Nitric Oxide (NO) scavenger and suppressor in cases where NO is elevated to supraphysiological levels, which was suggested to be useful in reducing inflammation in humans [9].…”
Section: Introductionmentioning
confidence: 99%